Representation of an aggrieved legal entity that has suffered damage as a result of a criminal offence at the stage of pre-trial investigation (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The article defines the concept and essence of representation of a legal entity in respect of which a criminal offence or a socially dangerous act has been committed. It is proposed that representation of a legal entity in respect of which a criminal offence or a socially dangerous act has been committed should be understood as a type of procedural activity of a legally authorized entity whose powers are duly certified and consist in ensuring the exercise of rights and obligations of this legal entity. It is determined that the essence of the activities of a legal entity's representative corresponds to the activities of a victim in criminal proceedings, since the involved representative enjoys the rights and obligations guaranteed by law to the victim. That is, at the stage of pre-trial investigation, he or she is authorised to file statements and complaints, submit evidence, participate in investigative (search) and procedural actions, receive copies of criminal proceedings and procedural decisions, etc.This article establishes that representation of legal entities in criminal proceedings requires two grounds: factual, which implies that a criminal offence has been committed against a legal entity which caused property damage, and legal, which implies the existence of a relevant document provided for in Part 3 of Article 58 of the CPC of Ukraine, by which a specific person is authorised to take actions aimed at exercising the rights and legitimate interests of a legal entity.The textual analysis of the provisions of Part 1 of Art. 303 of the CPC of Ukraine provided the basis for stating that the wording used by the legislator in paragraph 1, in particular, regarding the possibility of appealing against the inaction of an investigator, detective, or prosecutor, which consists in the failure to perform other procedural actions which he or she is obliged to perform within the time limit specified by the CPC of Ukraine, is incorrect. The emphasis is placed on the fact that, given the laws of formal logic, it may be subject to an extended interpretation, and therefore is the basis for the formation of ambiguous case law. In addition, the typical mistakes made by persons involved in representation of a legal entity are summarised.
Keywords: criminal procedure; victim; legal entity; victim's representative; proof; lawyer.